Cardiac Effects of a Single Dose of Pimobendan in Cats With Hypertrophic Cardiomyopathy; A Randomized, Placebo-Controlled, Crossover Study - Oldach, Maureen S.; Ueda, Yu; Ontiveros, Eric S.; Fousse, Samantha L.; Harris, Samantha P.; Stern, Joshua A. (Frontiers in Veterinary Science, 2019)
Background: Pimobendan has been shown to impart a significant survival benefit in cardiomyopathic cats who receive it as part of heart failure therapy. However, use of pimobendan remains controversial in cats with hypertrophic cardiomyopathy (HCM) due to lack of pharmacodynamic data for pimobendan in cats with HCM and due to theoretical concerns for exacerbating left ventricular outflow tract obstructions. Hypothesis/objectives: Our objective was to investigate the cardiac effects of pimobendan in cats with HCM. We hypothesized that pimobendan would not exacerbate left ventricular outflow tract obstructions and that it would improve echocardiographic measures of diastolic function. Animals: Thirteen purpose-bred cats were studied from a research colony with naturally-occurring HCM due to a variant in myosin binding protein C. Methods: Cats underwent two examinations 24 hours apart with complete standard echocardiography. On their first day of evaluation, they were randomized to receive oral placebo or 1.25 mg pimobendan 1 hour prior to exam. On their second examination, they were crossed over and received the remaining treatment. Investigators were blinded to all treatments. Results: The pimobendan group had a significant increase in left atrial fractional shortening (pimobendan group 41.7% + 5.9; placebo group 36.1%+ 6.0; p=0.04). There was no significant difference in left ventricular outflow tract (LVOT) velocities between the groups (pimobendan group 2.8 m/s + 0.8; placebo group 2.6 m/s + 1.0). There were no significant differences between the number of cats with LVOT obstructions between groups (12 in pimobendan group; 11 in placebo group; p=1.00). There were no detectable differences in any systolic measures, including left ventricular fractional shortening, mitral annular plane systolic excursion, and tricuspid annular plane systolic excursion. Doppler-based diastolic function assessment was precluded by persistent tachycardia. Conclusions: Improved left atrial function in the pimobendan group could explain some of the reported survival benefit for HCM cats in CHF. Pimobendan did not exacerbate LVOT obstructions and thus may not be contraindicated in HCM cats with LVOT obstructions. Future studies are needed to better characterize other physiologic effects, particularly regarding diastolic function assessment, and to better assess safety of pimobendan over a longer time-course.